The Pandemic and the “Perpetual Foreigner”: How Threats Posed by the COVID-19 Pandemic Relate to Stereotyping of Asian Americans - Daley, Jordan S.; Gallagher, Natalie M.; Bodenhausen, Galen V. (Frontiers in Psychology, 2022)
We examined the “othering” of Asian Americans in the context of the COVID-19 pandemic. Given past evidence that pathogen-related threat perceptions can exacerbate intergroup biases, as well as salient public narratives blaming the Chinese for the pandemic, we assessed whether individuals experiencing a greater sense of threat during the pandemic were more likely to apply the “perpetual foreigner” stereotype to Asian Americans. Over a seven-week period, we recruited 1323 White Americans to complete a measure of the perceived Americanness of Asian, Black, and White targets. Asian targets were consistently perceived as less American than White targets, across variations in subjective health threat and regional case counts. The direct and indirect connections of political ideology to the observed patterns were examined, revealing that White participants who blamed China for the pandemic were more likely to apply the perpetual foreigner stereotype to Asian Americans. These results indicate that the othering of Asian Americans is pervasive among White Americans and that variables related to social conditions surrounding the COVID-19 pandemic can predict the potency of this association.